TINJAUAN HUKUM MENGENAI PERLINDUNGAN KONSUMEN PAKAIAN BEKAS YANG DI IMPOR KE INDONESIA - Ajitya, Liscka elvera; ukas (LPPM Universitas Putera Batam, 2022)
Selling used clothing is generally an illegal activity. This has been regulated in the Law on Trade which states that every importer is obliged to import goods in new condition. From the provisions of the Trade Law that have been described, a conflict arises where other rules contradict the rules in the Consumer Protection Act called imported goods that still allow business actors to market used goods (including clothing) if they have provided complete and accurate information. This study aims to determine Consumer Protection based on the Law on Consumer Protection. This study uses the author using a type of normative juridical research. The normative juridical research was chosen by the author because the research was carried out by examining library materials through data collection procedures and analysis of laws and regulations to organize and process various legal materials that are in harmony with the formulation of the problem being studied in the preparation of this study. And the legal form that can be taken by consumers can be litigation or non-litigation dispute resolution.